Influence of bankruptcy prediction and residual income on company share prices in various industry sectors - Shinta Disky Azzharah (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
Research use the panel data regression analysis model aims to determine the predictions of bankruptcy with the Altman Z-Score model and residual income influence the stock prices of companies listed in the Indonesian Syariah Stock Index (ISSI) in the period 2014 to 2018. Research This is a quantitative study using secondary data in the form of annual financial statements published by companies, with sampling using purposive sampling to obtain a sample of 23 manufacturing companies engaged in various industrial sectors. The research method uses the fixed effect model approach. The analysis said that the bankruptcy prediction using the Altman Z-Score model showed a significant negative effect on stock prices, while residual income had no effect on stock prices. In addition, the Altman Z-Score shows that many companies enter the gray area cut-off point and even go bankrupt, thus making shareholders reduce their share prices for the safety of their shares in the capital market.